Do we need a new great transformation? Is one likely? - Frances Stewart (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Karl Polanyi wrote The Great Transformation in 1944 which analysed the double movement Europe experienced, from a situation where the market was heavily regulated and controlled in the eighteenth century to a virtually unregulated market in the nineteenth century, and the huge transformation in which the market was once more brought under control as a reaction to the poverty, unemployment and insecurity brought about by the unregulated market. Yet in both developed and developing countries there has since been a reaction with a new move towards the market. This paper analyses such processes in contemporary developing countries, and considers whether, in the light of the consequences of the unregulated market, a new Great Transformation is needed. It also considers whether such a transformation is likely, reviewing moves towards increased regulation of the market, and also the challenges faced by any contemporary great transformation arising from globalization and the nature of politics. – markets ; social protection ; regulation ; transformation
Keywords: O10; 330; Systemtransformation